Suicide risk in patients undergoing hemodialysis: a systematic review and meta-analysis of prevalence - Luigi Zerbinati; Federica Caccia; Federica Baciga; Martino Belvedere Murri; Pasquale Esposito; Rosangela Caruso; Ionut Nistor; Bjorn Meijers; Carlo Basile; Christian Combe; Luigi Grassi; Alessandro Mantovani; et al. (Renal Failure, 2025)
Background Kidney failure is strongly associated with psychological disorders, including anxiety, depression, and suicidal ideation. However, the prevalence of suicide risk in patients undergoing dialysis has not been fully established.Methods We performed a systematic review and meta-analysis aimed at assessing the prevalence of suicide risk in adult patients on dialysis and any correlation with demographic and clinical parameters.Results Twelve unique cross-sectional studies involving 1259 adult patients on dialysis were included. All patients were receiving hemodialysis treatment. In univariate meta-regression analysis, no significant effect of age, sex, and percentage of patients with diabetes mellitus on the prevalence of suicide risk was found. Overall, the prevalence of suicide risk was 20.6%. It varied widely, ranging from 4.0% to 57.3%, depending on the tools used (i.e. clinical interviews or self-report questionnaires). Among studies with more or less than 40% of patients on dialysis with anxiety and depression, the prevalence of suicide risk was very similar (21.2% vs 20.4%, respectively). The prevalence of suicide risk was more than double in lower-income than in higher-income countries (33.5% vs 15.3%, respectively).Conclusions The present systematic review and meta-analysis is a pioneering effort to identify the prevalence of suicide risk in patients on dialysis. It revealed a significant prevalence of suicide risk among hemodialysis patients, with a rate notably higher than that observed in the general population. This elevated risk is influenced by a complex combination of biological, psychological, and socio-economic factors.